2019
DOI: 10.1038/s41586-019-1464-0
|View full text |Cite
|
Sign up to set email alerts
|

Pol II phosphorylation regulates a switch between transcriptional and splicing condensates

Abstract: The synthesis of pre-mRNA by RNA polymerase II (Pol II) involves the formation of a transcription initiation complex and a transition to an elongation complex 1 – 4 . The large subunit of Pol II contains an intrinsically disordered C-terminal domain (CTD), which is phosphorylated by cyclin-dependent kinases (CDKs) during the initiation-to-elongation transition, thus influencing the CTD’s interaction with different components of the initiation or the RNA spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
474
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 523 publications
(536 citation statements)
references
References 39 publications
18
474
1
1
Order By: Relevance
“…1A) (Alston et al, 2004). The far UV CD spectrum of the hCPEB3 IDR also shows the hallmarks of a disordered protein, namely a minimum near 200 nm (Denning et al, 2003). No spectral features indicative of a-helix and b-sheet; namely, minima at 208, 218 or 222 nm and no maximum at 195 nm, are evident (Sup .…”
Section: Resultsmentioning
confidence: 97%
“…1A) (Alston et al, 2004). The far UV CD spectrum of the hCPEB3 IDR also shows the hallmarks of a disordered protein, namely a minimum near 200 nm (Denning et al, 2003). No spectral features indicative of a-helix and b-sheet; namely, minima at 208, 218 or 222 nm and no maximum at 195 nm, are evident (Sup .…”
Section: Resultsmentioning
confidence: 97%
“…Coupling between elongation and RNA processing through Pol II CTD becomes even more relevant considering recent findings that the CTD undergoes liquid-liquid phase separation (LLPS) Lu et al, 2018). LLPS of unphosphorylated CTD may facilitate Pol II clustering and transcriptional bursting during transcription initiation, whereas the subsequent LLPS wave of pS2-phosphorylated CTD may trigger Pol II clustering with RNA processing factors (Guo et al, 2019). PHF3 may promote the second wave of CTD LLPS through direct binding to pS2 CTD and RNA processing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we examined whether the LLPS-dependent membrane-free intranuclear compartments, such as Cajal bodies and splicing speckles, were affected by 1,6-HD treatment. These compartments were choosen because they were reported to be sensitive to 1,6-HD (Lin et al 2016;Guo et al 2019). The indirect immunofluorescence analysis of coilin, a major proteinaceous component of Cajal bodies, showed that 1,6-HD treatment (5%, 15 min), but not the treatment with Tween 20 alone, disrupted these compartments in living cells ( Fig.…”
Section: -Hd Treatment Of Living Cells To Study Higher-order Chrommentioning
confidence: 99%